Identifikaasi Tingkat Kerusakan Peralatan Laboratorium Komputer Menggunakan Metode Rough Set - Hengki Juliansa; Sarjon Defit; Sumijan Sumijan (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Computer laboratory is a means to support college pratikum. This equipment should always be in a ready-made state or suiTabel for use, whether computer or other means. In case of damage, it should be promptly resolved. To further accelerate the handling of damage, it is necessary a method to identify it. The Rought set method is a solution for this identification by means of several stages: Infomation System; Decision System; Equivalence Class; Descernibilty matrix and Descernibilty matrix of module D; Reduction; Generate Rules. The results of this study from 5 equipment in the computer laboratory STMIK Bina Nusantara Jaya Lubuklinggau after performing the steps of settlement by rough set method found 8 rules to get a new decision is whether the equipment is still worthy of use, repaired or replaced, then this method is very suiTabel applied in identifying the extent of damage.